2015
DOI: 10.1039/c5ra03575a
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on confinement effects of graphene and graphene oxide on structure and dynamics of water

Abstract: A snapshot of the formation of hydrogen bond between water molecules and the hydroxyl groups of the graphene oxide. Red, blue, and green colors correspond to oxygen, hydrogen, and carbon atoms, respectively. Dashed line show the hydrogen bond.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 45 publications
4
22
0
Order By: Relevance
“…3. Marti et al have shown that the water self-diffusivity in confined nanogap size of L z ¼ 3.1 nm at T ¼ 300 K is hDi ¼ 3.8 Â 10 À9 m 2 /s using flexible SPC model, which agree TIP3P results of this study, 34 and Zokaie and Foroutan have shown hDi ¼ 1.9 Â 10 À9 m 2 /s for L z ¼ 2.0 nm at T ¼ 300 K using the TIP4P/Ice water model, 74 which agrees SPC/E results of this study.…”
Section: -4supporting
confidence: 87%
See 3 more Smart Citations
“…3. Marti et al have shown that the water self-diffusivity in confined nanogap size of L z ¼ 3.1 nm at T ¼ 300 K is hDi ¼ 3.8 Â 10 À9 m 2 /s using flexible SPC model, which agree TIP3P results of this study, 34 and Zokaie and Foroutan have shown hDi ¼ 1.9 Â 10 À9 m 2 /s for L z ¼ 2.0 nm at T ¼ 300 K using the TIP4P/Ice water model, 74 which agrees SPC/E results of this study.…”
Section: -4supporting
confidence: 87%
“…The bulk water self-diffusivities and error bars are also shown. Other MDS results are also shown 34,74. 194302-5 M. Moulod and G. Hwang J. Appl.…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…Moreover, water molecules present in different regions of GO display different behaviors. For example, regions close to the GO surface are isolated, and other regions distant from the GO surface are surrounded by water molecules [6].…”
Section: Introductionmentioning
confidence: 99%